Electric machines principles, applications And control schematics - Zorbas, Dino (Cencage Learning, 2015)
Suitable for a single semester undergraduate course on electromechanical energy conversion devices or electric machines, this title strikes a balance between theoretical coverage, easy explanations, and practical applications, presenting real world applications of concepts without compromising on the rigor or the continuity of the text